Primary lateral sclerosis-like picture in a patient with a remote history of anti-N-methyl-D- aspartate receptor (anti-NMDAR) antibody encephalitis. (10th June 2018) - Janmohamed, Mubeen; Knezevic, Wally; Needham, Merrilee; Salman, Sam
Abstract : Anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis is a well-recognised disorder, first fully characterised in 2007. The long-term sequelae reported thus far include relapses with typical, as well as partial aspects of the well-defined neuropsychiatric syndrome. Rarely, isolated atypical symptoms (diplopia, ataxia and tremor) have been reported as relapse phenomenon. We report a case of a patient with a remote history of likely anti-NMDAR encephalitis with the longest follow-up reported in the literature to date (22 years). The relapse presentation was of a purely upper motor neuron syndrome with a primary lateral sclerosis-like picture.